Climate change mitigation : greenhouse gas reduction and biochemicals - Faria Albanese, Jimmy Alexander; Ruiz, M. Pilar (Apple Academic Press, 2015)
Climate change is a significant threat to humanity's future. Culturally, politically, economically, and personally, however, we are all deeply embedded in a system that continues to send us on a collision course that leads directly toward this threat. At this point, climate change is inevitable. What we must do now is to find ways to prepare-and do all we can to slow our race to disaster. This means that a transition to a lower-carbon economy is unavoidable.Biochemical research is vitally necessary for the transition we must make, and it will be an essential component of any climate policy. To.
Keywords: Climate change mitigation.; Climatic changes.; elektronické knihy; electronic books